Artificial intelligence (AI) technology in OpenAI ChatGPT application: A review of ChatGPT in writing English essay (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
ChatGPT is a product of AI that is currently being widely discussed on Twitter. This research reviews how ChatGPT writes English essays. This research is descriptive qualitative. The analysis shows that we can access ChatGPT on openai.com or chat.openai.com on the browser. If we do not have an account, we register via email, Google, or Microsoft account. After login, enter a question or statement in the conversation column provided. Send it and ChatGPT will respond and the answer appear quickly. The researcher tries ChatGPT “Can you help me in doing my English assignment?